2001
DOI: 10.1073/pnas.051003698
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone inhibits early atherogenesis by conversion to estradiol: Critical role of aromatase

Abstract: The effects of testosterone on early atherogenesis and the role of aromatase, an enzyme that converts testosterone to estrogens, were assessed in low density lipoprotein receptor-deficient male mice fed a Western diet. Castration of male mice increased the extent of fatty streak lesion formation in the aortic origin compared with testes-intact animals. Administration of anastrazole, a selective aromatase inhibitor, to testes-intact males increased lesion formation to the same extent as that observed with orchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
163
4
5

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(182 citation statements)
references
References 37 publications
10
163
4
5
Order By: Relevance
“…We subsequently demonstrated this possibility in LDLR Ϫ/Ϫ male mice and further demonstrated that this attenuating effect of testosterone on atherogenesis was abolished in the presence of an inhibitor of aromatase (8). The present work was undertaken to elucidate the cellular mechanism by which testosterone attenuates atherogenesis.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…We subsequently demonstrated this possibility in LDLR Ϫ/Ϫ male mice and further demonstrated that this attenuating effect of testosterone on atherogenesis was abolished in the presence of an inhibitor of aromatase (8). The present work was undertaken to elucidate the cellular mechanism by which testosterone attenuates atherogenesis.…”
mentioning
confidence: 78%
“…RNA extraction and purification were done by using RNeasy mini kit as described by the manufacturer's protocol (Qiagen, Chatsworth, CA). Total cellular RNA (3 g) was used for RT-PCR analysis of human aromatase with 50 units of Moloney murine leukemia virus reverse transcriptase at 42°C for 25 min, as described (8). The resulting cDNA samples were PCRamplified with the Gene Amp RNA PCR kit (Perkin-Elmer) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…94 Regarding the role of AR, conflicting findings have been reported. Nathan et al 95 demonstrated the inhibitory effects of testosterone on fatty streak formation in castrated low-density lipoprotein receptor-deficient male mice, but the effects of testosterone were abrogated by treatment with an aromatase inhibitor, suggesting that estradiol converted from testosterone had a major role. Conversely, Qiu et al 91 showed that nonaromatizable dihydrotestosterone suppressed atherosclerosis formation in castrated male rabbits, indicating a role for AR.…”
Section: Direct Effects Of Testosterone On Vascular Wallsmentioning
confidence: 99%
“…Conversely, testosterone is also a major biosource of estrogens, whereby testosterone can be aromatised to estradiol [71]. Therefore, it has been proposed that cardioprotection afforded by androgens could be mediated through aromatisation to estradiol and signalling through the ER [72]. Given that E2 is a regulator of the PTGIR and the hIP promoter (PrmIP) contains a highly conserved functional ERE [23], the more active metabolite DHT which cannot be converted to estradiol by aromatase was used throughout this study.…”
Section: Discussionmentioning
confidence: 99%